Body Mass and Fat Mass in Refractory Asthma: An Observational 1 Year Follow-Up Study - Bafadhel, Mona (Hindawi Publishing Corporation, 2010)
Background. Asthma and obesity are common; however the impact of obesity upon asthma remains uncertain. Objectives. To assess relationships between obesity and fat mass with airway inflammation, lung function, and disease control in patients with refractory asthma. Methods. 151 refractory asthma patients were characterised for measures of airway inflammation, lung function, Juniper asthma control questionnaire (JACQ), body mass index (BMI), and fat mass index (FMI) derived from dual energy X-ray absorptiometry. Patients were reassessed over 12 months. Results. 74% of patients had an elevated BMI. BMI and FMI correlated (r = 0.9, P < .001). FMI and JACQ correlated in men (r = 0.3, P = .01). After 12 months 23% lost weight. Weight change over 12 months correlated with FEV(1) change (r = −0.3, P = .03), but not with change in JACQ or exacerbations. Conclusion. Increased fat mass is common in refractory asthma and is associated with asthma symptom control in men. Loss of weight is associated with improvement in lung function in refractory asthma.